Fungal dominance of gross nitrogen mineralisation in an acidic upland soil amended with organic fertiliser. (18th July 2022) - Wang, Jing; Fu, Ruibiao; Li, Yong; Tu, Xiaoshun; Chen, Zhaoxiong; Elrys, Ahmed S.; Cheng, Yi; Zhang, Jinbo; Cai, Zucong; Müller, Christoph; Ma, Lifeng
Abstract: Fungi typically prevail in acidic soils and have a stronger preference for complex organic compounds than bacteria. Thus, we hypothesized that fungi would play a more important role in gross nitrogen (N) transformation in acidic soil than bacteria, and the dominance of fungi on gross N transformations in acidic soil would increase following complex organic inputs. Herein, we determined bacterial and fungal contributions to gross N transformation processes using a 15 N tracing approach combined with selective inhibition in an acidic upland soil under aerobic conditions. Streptomycin was used as the bacterial inhibitor and cycloheximide as the fungal inhibitor. Our results showed that bacteria appeared to dominate autotrophic nitrification but fungi were also involved, and both bacteria and fungi contributed to the gross rate of dissimilatory nitrate reduction to ammonium (NH4 + ). When rape seed cake was added to the soil, fungi dominated gross N mineralisation and played an important role in gross NH4 + immobilisation. Our results suggest that the addition of organic fertiliser into acidic upland soil can enhance the contribution of fungi to the mineralisation‐immobilisation turnover of N. Highlights: Bacterial and fungal contributions to gross N transformation rates were quantified. Bacteria dominated autotrophic nitrification in acidic upland soil. Fungi dominated gross N mineralisation following organic fertiliser addition. Adding complex carbon to acidic soil boosts fungal‐mediated N transformations.